MicroRNA-146a: A Comprehensive Indicator of Inflammation and Oxidative Stress Status Induced in the Brain of Chronic T2DM Rats - Yangmei Xie; Aiqun Chu; Yonghao Feng; Long Chen; Yiye Shao; Qiong Luo; Xiaolin Deng; Men Wu; Xiaohong Shi; Yinghui Chen (Frontiers Media S.A., 2018)
Objective: It was demonstrated that inflammation and oxidative stress induced by hyperglycemia were closely associated with alteration of miR-146a. Here, we investigated the role of miR-146a in mediating inflammation and oxidative stress in the brain of chronic T2DM rats.Methods: The chronic T2DM (cT2DM) models were induced by intraperitoneal administration of STZ (35 mg/kg) after being fed a high-fat, high-sugar diet for 6 weeks. H&E staining was conducted to observe the morphological impairment of the rat hippocampus. The expressions of inflammatory mediators (COX-2, TNF-α, IL-1β) and antioxidant proteins (Nrf2, HO-1) were measured by western blot. The levels of MDA and SOD were detected by the respective activity assay kit. The levels of p22phox and miR-146a were examined by quantitative real-time PCR (qRT-PCR). The expressions of IRAK1, TRAF6 and NF-κB p65 were measured by western blot and qRT-PCR. Pearson correlation analysis was performed to investigate the correlations between miR-146a and inflammatory mediators as well as oxidative stress indicators.Results: The expression of miR-146a was negatively correlated with inflammation and oxidative stress status. In the brain tissues of cT2DM rats, it was observed that the expressions of inflammatory mediators (COX-2, TNF-α, IL-1β) and oxidative stress indicators including MDA and p22phox were elevated, which were negatively correlated with the expression of miR-146a. While, the antioxidant proteins (Nrf2, HO-1, SOD) levels decreased in the brain of cT2DM rats, which were positively correlated with the miR-146a level. The expressions of NF-κB p65 and its specific modulators (IRAK1&TRAF6) were elevated in the brain of cT2DM rats, which might be inhibited by miR-146a.Conclusion: Our results implied that increased inflammation and oxidative stress status were associated with brain impairment in cT2DM rats, which were negatively correlated with miR-146a expression. Thus, miR-146a may serve as a negative comprehensive indicator of inflammation and oxidative stress status in the brain of chronic T2DM rats.